Uma breve introdução ao estudo da análise do Rn - Mendes, Adim Martins (2017)
Analysis is one of the most fertile branches of mathematics, with its rigor brings foundation for new concepts developed. The objective of this work is to study of the n-variables real functions, providing the reader a rst contact with the matter. We have introduced important concepts and theorems, emphasizing the notions of topology. Moving on to studying some continuous and di erentiable applications, reaching the mean value inequality.